Exploring the "Demand Side" of Online Radicalization: Evidence from the Canadian Context. (2nd July 2020) - Bastug, Mehmet F.; Douai, Aziz; Akca, Davut
Abstract: We examined whether and how social media play a role in the process of radicalization, and whether and for what purposes extremists use social media after they become radicalized within a sample of fifty-one Canadian extremists. Differences between converts and non-converts in terms of their radicalization process, involvement in terrorism, and social media usage were also investigated. Data were collected from a combination of media reports via an in-depth LexisNexis search and court records obtained from The Canadian Legal Information Institute database. The results confirm that social media played a role either during or after the radicalization process of the majority of the sample and converts are more vulnerable to online radicalization than non-converts.